Assessing essential service provision for prevention and management of violence against women in a remote indigenous community in Amantaní, Peru - Maria Calderon; Carla Cortez-Vergara; Laura Brown; Hattie Lowe; Blenda Abarca; Marta Rondon; Jenevieve Mannell (BMC, 2023)
Abstract Background Women living in indigenous communities in Peru currently experience extremely high rates of intimate partner violence (IPV). Over the past 10 years, there has been a large multi-sectoral initiative to establish a national network of Centros de Emergencia de la Mujer (Women's Emergency Centres) that integrate health and police services, and substantial increase in efforts from non-governmental organisations in supporting survivors of violence. However, there is currently little evidence on how existing services meet the needs of indigenous women experiencing violence in Peru. Methods As part of a broader mixed-methods participatory VAWG prevention study, we assessed existing service provision for women experiencing violence in an indigenous Quechua community from Amantaní, Peru. This involved 17 key informant interviews with legal, government, police, and civil society representatives. We used the UN Women Essential Services Package for Women and Girls Subject to Violence framework to guide our analysis. Results Participants identified major gaps in existing services for indigenous women survivors of violence in Peru. They discussed survivors and perpetrators not being identified by the health system, a lack of IPV response training for health professionals, IPV not being prioritised as a health concern, and a lack of health services that are culturally appropriate for indigenous populations. Survivors who report to police are often treated poorly and discriminated against. Legal systems were perceived as insufficient and ineffective, with inadequate legal measures for perpetrators. While legal and policy frameworks exist, they are often not applied in practice. Service provision in this region needs to adopt an intercultural, rights based, gendered approach to IPV response and prevention, considering cultural and linguistic relevance for indigenous populations. Conclusion The role of structural violence in perpetuating indigenous women's experiences of violence and undermining their access to services must be central to designing and implementing appropriate policies and services if they are to meet the needs of indigenous women in Peru.